The Effect of Core Learning Model on Students’ Metacognitive Skills in Lipid Material - Antika, Rindi Novitri (UIN Fatmawati Sukarno Bengkulu, 2020)
Metacognitive is one of the important factors must have by student. This study aims to determine the effect of the CORE (Connecting, Organizing, Reflecting, and Extending) learning model on students' metacognitive sklills and find out the students' responses about it’s implementation. This research is a pre experimental study with one group pretest-posttest design. The subject of this study was grade 3rd of biology education students. The instrument in this study is an essay and metacognition descriptor rubric to assess students' metacognitive skill, then questionnaires to obtain data on student responses that implemented the CORE learning model. Based on the results of the paired sample t test on student metacognition scores obtained sig. 0.00 <0.05, it means that there are differences between the results of the student's pretest and posttest. Then, based on N-gain analysis pretest and posttest data, it is known that the N-gain value is 0.71, it’s means high increase category,. Then the result of pearson correlation test to analyze correlation between cognitive learning outcomes and student metacognitive skills obtained sig. 0,00, it means that there was a correlation between the two of them. Based on some of these analyzes it can be concluded that the CORE learning model influences students' metacognitive skills on lipid material. This was supported by the results of a questionnaire showed that students gave positive responses about the application of the CORE learning model, it was known from questionnaire data, more than 85% of students felt the CORE model had a positive impact on learning.